The Role of Circulating Tumour Cells and Carcinoembryonic Antigen as Diagnostic Tool for Metastatic Colorectal Cancer in Indonesia - Angraeni, Sri; Abdullah, Murdani; Hasan, Irsan; Rinaldi, Ikhwan; Fauzi, Achmad; Martin, Cleopas; Shatri, Hamzah; Irawan, Cosphiadi; Nursyirwan, Saskia Aziza; Ibrahim, Febiansyah; Siregar, Lianda; Loho, Imelda Maria; Waspodo, Agus Sudiro; Margaluta, Ariansah; Firsyada, Fajar; Darnindro, Nikko; Lutfiah, Evah; Tanadi, Caroline; Ilyas, Mohammad (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2025)
Background: Patients with metastatic colorectal cancer (CRC) have a poor prognosis, with a 5-year survival rate of only 14%. Early detection and early intervention may improve outcome. Both circulating tumour cells (CTC) and serum carcinoembryonic antigen (CEA) have been suggested as diagnostic biomarkers for metastatic CRC. This study explored the performance of CTC and CEA as a tools for the detection of metastatic colorectal cancer in Indonesia.Methods: This study was conducted from December 2024 to April 2025 on metastatic colorectal cancer patients from three hospitals in Jakarta. CTC was analysed using the gradient density method and flow cytometry. CEA was analysed using chemiluminescent microparticle immunoassay.Results: This study recruited 160 patients with colorectal cancer patients of whom, 45% were known to have metastatic colorectal cancer. The median age was 57 (47—66) years and analysis was done at one time point only. The area under the curve (AUC) for CTC, CEA, and the combination of both CTC and CEA in diagnosing metastatic colorectal cancer was 0.579, 0.811, and 0.703, respectively. CTC showed 56.94% sensitivity and 50.00% specificity in detecting metastatic colorectal cancer. Meanwhile, CEA showed higher sensitivity (72.22%) and specificity (72.72%). Combination of both CTC and CEA increased sensitivity to 91.67%, but with a lower specificity of 37.50%. The optimal cut-off for CTC and CEA were 34.5 cells/3 ml and 18.31 ng/ml, respectively.Conclusion: CEA showed a better performance than CTC in diagnosing metastatic colorectal cancer. Combination of CTC and CEA showed promising potential as a valuable surveillance tool for detecting metastasis in colorectal cancers, but not as a primary diagnostic tool.